Does civil society matter for natural resource governance? A comparative analysis of multi-stakeholder participation and EITI validation outcomes. (August 2021) - Wilson, Christopher; Claussen, Christoffer; Valverde, Pablo
Abstract: The EITI leverages a multi-stakeholder model in which government, civil society and business collaborate to improve the quality of resource governance in participating countries. Like other multi-stakeholder initiatives that aim to improve public governance through information disclosure and civic participation, this model relies on an assumption that civil society participation in the process improves EITI outcomes. This assumption is tested through comparative analysis of data from 63 EITI Validation processes. The results indicate that civil society participation has a small but statistically significant correlation with EITI outcomes related to the rules and comprehensiveness of information disclosure, quality assurance processes, public debate, and most clearly in regard to the reforms that follow from the recommendations in Validations. There are, however, important differences between civil society's contributions to different outcomes, and whether or not civil society participation takes place within the multi-stakeholder group (MSG). Notably, restrictions on MSG participation are found to have a strong moderating effect on civil society's contributions to EITI outcomes, but restrictions on national civic space do not. The results suggest that the discourse surrounding the EITI has been overly simplistic in how it has considered the role of civil society and civic space, and would benefit from more precise consideration of different types of civil society engagement with national EITI processes. Highlights: Civil society participation in the EITI has a positive correlation with EITI outcomes. Participation inside multi-stakeholder groups differs from external participation. Internal participation makes a stronger contribution to accountability outcomes. Restrictions on multi-stakeholder groups limit the contributions of civil society. Restrictions on national civic space do not limit the contributions of civil society.